Current transients at a channel electrode produced by a potential step - Compton, R; Daly, P (1984)
A theory is presented which describes the transient current response to a potential step at a channel (or tubular) electrode for a reversible electrode reaction. Experimental results for a wide range of solution flow velocities are found to be in good agreement with theory.